European Microfinance – Relevance, Efficiency And Impact - Fila, Joanna (Comparative Economic Research. Central and Eastern Europe, 2015)
Microfinance aims at providing basic financial services such as loans, savings and insurance to socially and financially excluded persons and microentrepreneurs. Among these services, microcredit is the most recognizable instrument of microfinance. Microcredit supplies financial means to start up businesses and to finance microenterprises. Microfinance originated in poor countries. In recent years, however, it has also gained some recognition in European countries. This article presents the relevance, efficiency and impact of microfinance policy and its policy instruments with respect to support for microenterprises in the European Union.